Prolonged magmatism and growth of the Iran-Anatolia Cadomian continental arc segment in Northern Gondwana - Moghadam, H. Shafaii; Li, Q. L.; Griffin, W. L.; Stern, R. J.; Santos, J. F.; Lucci, F.; O'Reilly, S. Y. (Elsevier, 2021)
Much of the crust of Iran and Anatolia, including their oldest exposed rocks, formed during an episode of intense convergent margin (arc) magmatism as a result of subduction of oceanic lithosphere beneath northern Gondwana from ca 620 Ma to ca 500 Ma, the Cadomian crust-forming event. Most igneous rocks formed between ca 570 and 525 Ma. Cadomian crust is well-known from western and southern Europe and from eastern North America but is much less well-known from Iran and Anatolia. We use published age and compositional data and contribute new data in order to better understand this ancient magmatic system. Cadomian magmatism included calc-alkaline igneous rocks of arc affinity in the main arc and alkalic igneous rocks that formed in a back-arc setting; these igneous rocks are associated with sedimentary rocks. Geochemical and isotopic modelling reveals that basaltic magmas were the main input, that these formed by partial melting in the upper mantle, and that basaltic magmas evolved further in deep crustal hot zones to form granitic magmas through a combination of assimilating older continental crust and fractional crystalization of basaltic magmas. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Cadomian magmatism; Arc-like igneous rocks; Magmatic flare-up; Back-arc; Anatolia; Iran